The Effect of Audit Tenure, Audit Rotation and Head Reputation on Audit Quality - Fitri Fajar Riyani; Maidani; Novita Wahyu Setyawati; Cahyadi Husadha (Kusuma Negara Business School, 2021)
This study aims to examine the effect of audit tenure, audit rotation and KAP's reputation on audit quality. The type of data used in this study is secondary data, namely the data of financial statements of manufacturing companies listed on the Indonesia Stock Exchange in the period 2015 - 2018. The research method used is multiple linear regression analysis to test the effect of audit tenure, audit rotation and reputation of the public accountant firm. partial and simultaneous audit quality. Discretionary accruals are used as a proxy for audit quality. The results showed that simultaneous variables of audit tenure, audit rotation and KAP reputation did not significantly influence audit quality. While partially audit tenure and audit rotation have no effect on audit quality, and KAP reputation has a significant effect on audit quality.